(untitled) (Experimental biology, 2018)
The search for substances that inhibit the production of active forms of oxygen (ROS) and pro-inflammatory cytokines in conditions of ischemic brain injury, is of great practical importance for the therapy of post-stroke states. The purpose of this study is to study the effect of extract from Limonium gmelinii on the development of oxidative stress in human astrocytes and neurons of the human brain under the influence of the proinflammatory cytokine TNF-α in vitro. Methods of isolation and cultivation of human fetal cells, immunohistochemical, fluorescent methods for the qualitative and quantitative determination of the anion supeoxide in isolated neurons and astrocytes were used in the work. In the course of the study it was found that the extract from Limonium gmelinii at a dosage of 30 μg / ml does not have a cytocidal effect, moreover, it neutralizes the toxic effect of TNF-α: blocks the formation of ROS in neurons and astrocytes, prevents the activation of NADPH oxidase in astrocytes. Thus, the results of the conducted study allow us to conclude that the extract from Limonium gmelinii possesses antioxidant, astro- and neuroprotective properties and can be used for therapy of reperfusion syndrome. The results of the study are important for neurobiology and medicine.